CULTIVATING CIVIC VIRTUE AND SOCIAL ENGAGEMENT THROUGH STUDENT ORGANIZATIONS: EVIDENCE FROM IPNU SUMBER HARTA - Tri Irwanto; Erwin Rochmansyah; Agus Mukmin (STAI Asy-Syukriyyah, 2026)
The cultivation of civic virtue and social engagement among students is increasingly important in addressing social change, declining community participation, and the influence of digital culture. This study examines the role of Ikatan Pelajar Nahdlatul Ulama (IPNU) Sumber Harta in fostering civic virtue and strengthening students’ social engagement. Using a qualitative case study approach, data were collected through interviews, participant observation, and document analysis involving organizational advisors, former leaders, active administrators, and community figures. The findings indicate that IPNU promotes civic virtue through responsibility, discipline, tolerance, leadership, civic awareness, and commitment to the common good. The organization also enhances social engagement through religious activities, social services, charitable programs, and community participation initiatives. Supporting factors include strong leadership, value-based organizational culture, cadre development, and community support, while financial limitations and competing responsibilities remain challenges. Faith-based student organizations can serve as effective platforms for civic education and active citizenship development.